OPERATIONAL EVALUATION OF FERRY VESSELS TO IMPROVE SERVICES ON THE BASTIONG – SOFIFI TRAIN, NORTH MALUKU PROVINCE - Tungkup, Doharman Lumban; Firzatullah, Raden Muhamad; Saadila, Diva Meira (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2023)
Bastiong Ferry Port is a ferry port operating in the Ternate City Area of ​​North Maluku, which aims to accommodate the traffic needs of the community in the North Maluku National Strategic Area. The number of ships serving this route is 7 ships with a passenger load factor of 61% departure and 56% arrival. Meanwhile, the vehicle load factor is 577% for departure and 717% for arrival. This study uses a quantitative research method which aims to: 1) To determine the Load Factor of ships operating on the Bastiong-Sofifi route has reached an ideal condition, 2) To determine the number of ships operating on the Bastiong-Sofifi route that is in accordance with the level of demand for service users. The results of this study are that the prediction of passenger growth in 2023 has reached the planned Load Factor of 65% with a frequency of ship departures of 3 round trips/day so that it can be concluded that the number of ships operating on the Bastiong-Sofifi Route does not match the demand for existing transportation services. The solution to this problem is a recommendation for a new schedule on the Bastiong-Sofifi Route with the number of ships operating as many as 10 ships/day and during working hours, namely on Monday, an additional 1 trip.